Alexandria, Kom el-Dikka. Seasons 2014–2015. Appendix: Islamic cemetery at Kom el-Dikka in Alexandria: research in the 2014 and 2015 excavation seasons - Grzegorz Majcherek; Emanuela Kulicka (Polish Archaeology in the Mediterranean, 2017)
The Polish–Egyptian mission at Kom el-Dikka, ran by the Polish Centre of MediterraneanArchaeology, University of Warsaw, stepped up the already advanced preservation processesaimed at establishing an Archaeological Park at the site. Conservation work was carried out in thetheater portico, the bath complex and the residential quarter of late Roman date in the eastern partof the excavation area. In turn, the western part was the focus of archaeological research centeredon the exploration of some late Roman structures located underneath. The early medieval/Islamiccemetery overlying these remains was explored first. A detailed report from this work is appendedto this article. The human skeletal remains from the cemetery were examined by anthropologists.The western gate to the bath complex, leading from the theater portico, was fully exposed. Findsfrom present and earlier work at the site continued to be studied: glass vessels, pottery, lamps, boneobjects, painted wall plaster, and a vast collection of coins.